Two-year Results of Bronchoscopic Lung Volume Reduction Using One-Way Endobronchial Valves: Real-World Single Center Data - Bivort D; Blondeel A; Geysen H; Vandervelde CM; Coolen J; Ceulemans LJ; Dooms C; Janssens W; Everaerts S (International Journal of COPD)
Dorian Bivort,1,* Astrid Blondeel,2,3,* Hannelore Geysen,1 Christelle M Vandervelde,3,4 Johan Coolen,5 Laurens J Ceulemans,3,4 Christophe Dooms,1,3 Wim Janssens,1,3 Stephanie Everaerts1,3 1Clinical Department of Pulmonary Diseases, University Hospitals Leuven, Leuven, Belgium; 2Department of Rehabilitation Sciences, KU Leuven, Leuven, Belgium; 3Department of Chronic Diseases and Metabolism, BREATHE, KU Leuven, Leuven, Belgium; 4Clinical Department of Thoracic Surgery, University Hospitals Leuven, Leuven, Belgium; 5Clinical Department of Radiology, University Hospitals Leuven, Leuven, Belgium*These authors contributed equally to this workCorrespondence: Stephanie Everaerts, University Hospitals Leuven, Herestraat 49, 3000, Leuven, Belgium, Email stephanie.everaerts@uzleuven.beBackground: Bronchoscopic lung volume reduction (BLVR) using one-way endobronchial valves (EBV) is a minimally invasive treatment for patients with advanced emphysema and severe hyperinflation. While several randomized controlled trials have demonstrated improvements in lung function, exercise performance, and quality of life, information on long-term outcomes of BLVR outside clinical trial settings are limited.Objective: This study provides real-world data with a follow-up of up to two years, incorporating the BODE index (Body-Mass Index, Airflow Obstruction, Dyspnea, and Exercise Capacity Index), as part of the follow-up assessments.Methods: Data were collected for all patients treated with BLVR at the University Hospitals of Leuven, Belgium, including lung function parameters, 6-minute walking distance, respiratory questionnaires, and the BODE index at intervals of 3, 6, 12, and 24 months. A composite outcome combining FEV1 (forced expiratory volume in 1 second), 6MWD (6-minute walk distance), and SGRQ (St. George’s Respiratory Questionnaire) was used to evaluate the overall impact of BLVR. Mixed model analyses were performed.Results: All outcome parameters, including FEV1, residual volume (RV), 6MWD, modified Medical Research Council (mMRC) and SGRQ exhibited significant improvement up to 1 year of treatment. RV and mMRC maintained statistical significance compared to baseline at the 2-year follow-up. The BODE index as well, revealed a significant improvement persisting up to 2 years of treatment. Response rate for the composite outcome was 86% (44/51) at one year and 71% (17/24) at 2 years follow-up.Conclusion: Follow-up data of a real-world setting show maintained benefits of bronchoscopic lung volume reduction with endobronchial valves up to 2 years after treatment, for patients of whom the valves are still in situ. A potential survival benefit of BLVR, based on BODE, and high response rate on the composite outcome was present, in patients who remained in follow-up.Keywords: COPD, bronchoscopic lung volume reduction, emphysema